2020
DOI: 10.1186/s12906-020-2875-z
|View full text |Cite
|
Sign up to set email alerts
|

Ginger extract versus Loratadine in the treatment of allergic rhinitis: a randomized controlled trial

Abstract: Background: Allergic rhinitis (AR) is a non-infectious immune disease and incidents of the disease has continuously increased in Thailand. Ginger, a Thai herb, is used in food and Thai traditional medicine. This study was designed to assess efficacy and safety of ginger extract in comparison with loratadine for AR treatment. Methods: AR patients were treated with ginger extract 500 mg (n = 40) against those treated with loratadine 10 mg (n = 40) in a randomized, double-blind, controlled trial for 3 and 6 weeks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 20 publications
0
26
0
Order By: Relevance
“…A study on essential oil of ginger reported immunomodulatory effects by improving the humoral immunity in cyclophosphamide-immunosuppressed mice in a dose-dependent manner ( Carrasco et al, 2009 ). Oral administration of alcoholic ginger extract to allergic rhinitis patients showed significant reduction in total nasal symptom scores (TNSS), with overall improvement in rhino conjunctivitis quality of life questionnaire ( Yamprasert et al, 2020 ). The aqueous and alcoholic extracts of rhizome decreased goblet cell hyperplasia, infiltration of inflammatory cells in airways with reduced total and differential counts of eosinophils and neutrophils in mouse model ( Khan et al, 2015 ) ( Table 5 ).…”
Section: Ayush Recommendations For Management Of Covid-19mentioning
confidence: 99%
“…A study on essential oil of ginger reported immunomodulatory effects by improving the humoral immunity in cyclophosphamide-immunosuppressed mice in a dose-dependent manner ( Carrasco et al, 2009 ). Oral administration of alcoholic ginger extract to allergic rhinitis patients showed significant reduction in total nasal symptom scores (TNSS), with overall improvement in rhino conjunctivitis quality of life questionnaire ( Yamprasert et al, 2020 ). The aqueous and alcoholic extracts of rhizome decreased goblet cell hyperplasia, infiltration of inflammatory cells in airways with reduced total and differential counts of eosinophils and neutrophils in mouse model ( Khan et al, 2015 ) ( Table 5 ).…”
Section: Ayush Recommendations For Management Of Covid-19mentioning
confidence: 99%
“…There is no solid evidence for interactions with anti-coagulant drugs. Dizziness was described [51,52,55].…”
Section: Gingermentioning
confidence: 99%
“…Ginger is also associated with dizziness [55], increasing doubts about the solidity of the evidences.…”
Section: Gingermentioning
confidence: 99%
“…Loratadine sold under the brand name Claritin is used as the second-generation antihistamine for the symptomatic treatment of allergic rhinitis and chronic idiopathic urticaria and has no clinically significant sedative and anticholinergic effects [1,2]. By the chemical structure it is 4-(8-chloro-5,6-dihydro-11H-benzo [5,6]cyclohepta [1,2-b]pyridine-11-ylidene)-1-piperidinecarboxylic acid ethyl ester; thus, it belongs to the group of tricyclic selective blockers of peripheral H 1 -histamine receptors (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…Fritzand et al observed that the well-being of patients with malignant skin diseases (melanoma) could be improved by application of loratadine and its metabolite [4]. Another research group of Yamprasert et al determined that the combination of loratadine with the ginger extract had a positive effect on reducing nasal symptoms when treating allergic rhinitis [5]. Nayak et al evaluated the efficacy and safety of the loratadine syrup compared with the cetirizine syrup and made a conclusion that cetirizine was more effective, but loratadine had fewer side effects [6].…”
Section: Introductionmentioning
confidence: 99%